Różnice kulturowe w podejściu rodziców do trudności w uczeniu się ich dzieci oraz sposoby radzenia sobie z nimi – wprowadzenie do badania - Gonen-Avital , Shiri (Studia Edukacyjne, 2018)
The main aim of the article is to identify and explain the issues of parents’ attitudes and ways of coping with their situation as parents toLearning Disability children, in relation to the differentCultural parents. This article stems from a deep and extensive dissertation research on parents’ attitudes toward their child Learning Disability in Israel and it is presented as an outline of the research study. Studying the parents attitudes and coping with their child’s Learning Disability, is an important area that should generate interest among researchers. The family is the source of the child’s development, and the parents are responsible for the creation of his values and beliefs. In summary, the connections between Learning disability, society and culture, attitudes, stress and coping concerning the parents of children diagnosed as having Learning was discussed in this article. There is an urgent need to explore these parents’ varied cultures, their different beliefs, attitudes, and their characteristics. It is important to remember that the family is a supportive framework that protects the child. The best way to help the L.D. child and his family is through understanding the way in which they experience the disability at home, and in the community.